1973
DOI: 10.1073/pnas.70.4.1179
|View full text |Cite
|
Sign up to set email alerts
|

An RNA Polymerase Mutation Causing Temperature-Sensitive Sporulation in Bacillus subtilis

Abstract: A single-site mutant of Bacillus subtilis with a rifampin-resistant RNA polymerase has been isolated; this mutation causes temperature-sensitive sporulation. The temperature-sensitive mutation was only expressed during a limited time period, covering the middle third of the sporulation sequence. Mutant cells grown at the nonpermissive temperature exhibited the normal change in RNA polymerase template specificity, accumulated extracellular proteolytic activity and antibiotic activity, but failed to accumulate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

1974
1974
1982
1982

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 15 publications
1
25
0
Order By: Relevance
“…These problems may be studied by the use of temperature-sensitive mutants (19,20,31,32) that are shifted from permissive to nonpermissive conditions, and vice versa, during sporulation. Esposito et al (12), working with temperature-sensitive mutants ofSaccharomyces cerevisiae, showed that it is possible to make allowances for both (i) different rates of development at permissive and nonpermissive temperatures and (ii) different rates of development of different strains under identical conditions, so that the position in the sporulation sequence of the temperature-sensitive period of a mutant may be determined.…”
mentioning
confidence: 99%
“…These problems may be studied by the use of temperature-sensitive mutants (19,20,31,32) that are shifted from permissive to nonpermissive conditions, and vice versa, during sporulation. Esposito et al (12), working with temperature-sensitive mutants ofSaccharomyces cerevisiae, showed that it is possible to make allowances for both (i) different rates of development at permissive and nonpermissive temperatures and (ii) different rates of development of different strains under identical conditions, so that the position in the sporulation sequence of the temperature-sensitive period of a mutant may be determined.…”
mentioning
confidence: 99%
“…kinases), or other regulatory macromolecules that alter its specificity and allow it to transcribe sporulation-specific genes. A streptovaricin resistant RNA polymerase mutant which has a mutation close to the rifampicin locus also has a phenotype similar to that exhibited by the Class IV mutants (87); it was of interest that no streptolydigin-resistant RNA polymerase mutants were conditionally temperature sensitive during sporulation. Since streptolydigin only inhibits elongation and not initiation, it is possible that this function is identical in both vegetative and sporulation RNA polymerase molecules.…”
Section: Rna Polymerase Mutations Causing Asporogenymentioning
confidence: 97%
“…Leighton and his co-workers have used a more direct approach. They have isolated various ts mutants-of B. subtilis affecting specific enzymes which they believed were involved in sporulation (Leighton 1973;Leighton et nl. 1972Leighton et nl.…”
Section: Introductionmentioning
confidence: 98%
“…, 1973. One series of ts mutants isolated by Leighton (1973) include rifampin-resistant RNA polymerase mutants which are affected at uniquely different time periods during sporulation. One of them, ts-14, produces several of the products involved in the early stages of sporulation but is affected in forespore membrane synthesis and engulfment and synthesis of alkaline phosphatase (Leighton 1973;Santo et 01.…”
Section: Introductionmentioning
confidence: 99%